Substrate interactions of the electroneutral Na(+)-coupled inorganic phosphate cotransporter (NaPi-IIc) - Ghezzi, Chiara (Blackwell Science Inc, 2009)
The SLC34 solute carrier family comprises the electrogenic NaPi-IIa/b and the electroneutral NaPi-IIc, which display Na(+) : P(i) cotransport stoichiometries of 3 : 1 and 2 : 1, respectively. We previously proposed that NaPi-IIc lacks one of the three Na(+) interaction sites hypothesised for the electrogenic isoforms, but, unlike NaPi-IIa/b, its substrate binding order is undetermined. By expressing NaPi-IIc in Xenopus oocytes, isotope influx and efflux assays gave results consistent with Na(+) being the first and last substrate to bind. To further investigate substrate interactions, we applied a fluorometry-based technique that uses site-specific labelling with a fluorophore to characterize substrate-induced conformational changes. A novel Cys was introduced in the third extracellular loop of NaPi-IIc that could be labelled with a reporter fluorophore (MTS-TAMRA). Although labelling resulted in suppression of cotransport as previously reported for the electrogenic isoforms, changes in fluorescence were induced by changes in extracellular Na(+) concentration in the absence of P(i) and by changes in extracellular P(i) concentration in presence of Na(+). These data, combined with (32)P uptake data, also support a binding scheme in which Na(+) is the first substrate to interact. Moreover, the apparent P(i) affinity from fluorometry agreed with that from (32)P uptake, confirming the applicability of the fluorometric technique for kinetic studies of electroneutral carriers. Analysis of the fluorescence data showed that like the electrogenic NaPi-IIb, 2 Na(+) ions interact cooperatively with NaPi-IIc before P(i) binding, which implies that only one of these is translocated. This result provides compelling evidence that SLC34 proteins share common motifs for substrate interaction and that cotransport and substrate binding stoichiometries are not necessarily equivalent.